2017
DOI: 10.1016/j.chemer.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and petrogenesis of Soltan Maidan basalts (E Alborz, Iran): Implications for asthenosphere-lithosphere interaction and rifting along the N margin of Gondwana

Abstract: Soltan Maidan Basaltic Complex with thickness up to about 1300 m is located in the eastern Alborz zone, north of Iran. This complex is dominantly composed of transitional to mildly alkaline basaltic lava flows, agglomerates and tuffs, together with a few thin sedimentary interlayers. Field geological evidence and study of palynomorph assemblages in the shale interlayer show Late Ordovician to Early Late Silurian ages. Chondrite-and primitive-mantle normalized multi-element patterns of Soltan Maidan basalts dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
0
17
1
Order By: Relevance
“…Two major groups of Phanerozoic ages are also captured, one at ∼450 Ma, and the other at ∼280 Ma, but neither of them has been reported in adjacent regions within the Central Iran Block. Within Ordovician-Silurian strata, a thick layer of basalt to basaltic-andesite named the Soltan-Meidan Formation is present in the Eastern Alborz and the Binalud Mountains (Derakhshi et al, 2017;Ghaemi et al, 1999), but it lacks precise age constraints. Moghadam, Li, Griffin et al (2017) found similar ages in Devonian sandstone from the Eastern Alborz (Figure 9d), and correlated these ages to the erosion of Ordovician volcanic and intrusive rocks (Derakhshi et al, 2017).…”
Section: Provenance Shift In the Triassic And Jurassic Rocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Two major groups of Phanerozoic ages are also captured, one at ∼450 Ma, and the other at ∼280 Ma, but neither of them has been reported in adjacent regions within the Central Iran Block. Within Ordovician-Silurian strata, a thick layer of basalt to basaltic-andesite named the Soltan-Meidan Formation is present in the Eastern Alborz and the Binalud Mountains (Derakhshi et al, 2017;Ghaemi et al, 1999), but it lacks precise age constraints. Moghadam, Li, Griffin et al (2017) found similar ages in Devonian sandstone from the Eastern Alborz (Figure 9d), and correlated these ages to the erosion of Ordovician volcanic and intrusive rocks (Derakhshi et al, 2017).…”
Section: Provenance Shift In the Triassic And Jurassic Rocksmentioning
confidence: 99%
“…Within Ordovician-Silurian strata, a thick layer of basalt to basaltic-andesite named the Soltan-Meidan Formation is present in the Eastern Alborz and the Binalud Mountains (Derakhshi et al, 2017;Ghaemi et al, 1999), but it lacks precise age constraints. Moghadam, Li, Griffin et al (2017) found similar ages in Devonian sandstone from the Eastern Alborz (Figure 9d), and correlated these ages to the erosion of Ordovician volcanic and intrusive rocks (Derakhshi et al, 2017). In contrast, our Devonian and Permian samples do not contain any Ordovician-Silurian age information, and if the Soltan-Meidan Formation was exposed in Triassic and provided Ordovician-Silurian ages, there should also be Pan-African ages transported from Devonian sandstone to Triassic samples.…”
Section: Provenance Shift In the Triassic And Jurassic Rocksmentioning
confidence: 99%
“…These include the ca. 450 Ma (457 ± 34 Ma -379 ± 27 Ma) Suordakh dolerite event in eastern Siberia (Khudoley et al, 2013;Chamberlain et al, 2018), the Ongnyeobong Formation volcanics in South Korea (Cho et al, 2014), flood basalts of Sierra del Tigre in Argentina (González-Menéndez et al, 2013;Retallack, 2015), and the intraplate basaltic lava flows of the Soltan Maidan Basaltic Complex with thickness up to about 1,300 m located in the eastern Alborz zone, north of Iran (Derakhshi et al, 2017). More precise and better age determinations are required to test the link to the Hirnantian glacial maximum and Late Ordovician mass extinction.…”
Section: The Hirnantian Glaciation (Ca 440 Ma)mentioning
confidence: 99%
“…This conclusion can also be supported by the diagram of Sm vs. Sm/Yb (Figure 8b). [58]). The data of Kafang from [16].…”
Section: Petrogenesismentioning
confidence: 99%
“…Figure 9. (a) Zr vs. Nb diagram (modified from [58]); (b) CaO/Al 2 O 3 vs. Al 2 O 3 diagram (modified from [40]), ol: olivine, cpx: clinopyroxene; (c) Sc vs. Ti/Y diagram (modified from [7]); (d) Mg# vs. TFe 2 O 3 diagram; (e) Mg# vs. TiO 2 diagram; (f) ( 87 Sr /86 Sr)i vs. ( 143 Nd/ 144 Nd)i (modified from[58]). The data of Kafang from[16].…”
mentioning
confidence: 99%